The Role of the Dividend Payout Ratio as a Stock Price Mediation - Lisa, Oyong; Farhan, Djuni; Indrasmono, Malikoes Arisnadi (Mahameru Publisher, 2023)
Stock prices in the capital market are based on the interaction between supply and demand. When there is a high demand for a stock, the price usually goes up, while an oversupply of stock causes the price to fall. The closing price is the market price when the transaction is completed at the end of the day as a result of an agreement between the buyer and the seller. Therefore, the closing price is used as the share price in research related to stock prices. The purpose of this study was to analyze the role of the Dividend Payout Ratio (DPR) as a mediating effect of Earning Per Share (EPS) and Return on Assets (ROA) on Stock Price (SP). Using an explanatory research approach, this research was conducted at the Jakarta Indonesia Stock Exchange on listed banking companies in 2016-2021. The population is 43 companies, using a purposive sampling technique, 12 companies are obtained, so a total of 72 companies during 2016-2021. Secondary data in the form of the company's financial statements were obtained by means of documentation techniques through access to idx.co.id. Next, it is analyzed with path analysis. The results prove that the DPR is able to mediate or increase the influence of EPS and ROA on SP.